IMPLEMENTASI AKUNTANSI BERBASIS AKRUAL SEBAGAI MODEL PEMBELAJARAN VOKASIONAL DI MA TARBIYATUL MUSTAFID - Ihyani, Layali; Saputra, Sahdan; Marswandi, Ega Dwi Putri; Marlina, Febria Nurmelia; Mubin, Miftahul; Komala, Rina (Universitas Mataram, 2025)
This community service activity aims to improve the financial literacy of Social Sciences (IPS) students through the application of accrual-based accounting records, using a participatory socialization method. The background of this activity stems from the phenomenon that accounting education in secondary schools is still predominantly cash-based, making it difficult for students to distinguish between income and cash receipts, resulting in limited experience in recording complex transactions. The identified research gap is the limited study of the implementation of accrual accounting in the context of secondary education, especially among IPS students, even though this competency is highly relevant to modern accounting demands. The activity was carried out at MA Tarbiyatul Mustafid Baturimpang, Narmada District, involving 21 students from Class XII IPS-2. The implementation method consisted of three stages: theoretical explanation, simulation of transaction-recording practices, and evaluation through pre- and post-tests. The results showed a significant increase in students' understanding, with the average pre-test score rising from 45 to 78 in the post-test score. A total of 72% of students were able to apply accrual principles in simple case studies, and 85% of the groups successfully prepared accrual-based financial statements. Participant responses were also very positive, with 88% stating that the material was easy to understand, and 92% expressing interest in practicing it in daily life. The novelty of this activity lies in the integration of accrual practice into students’ daily simulations through a participatory approach, which has rarely been implemented in high school curricula. These findings not only strengthen students’ accounting competencies but also offer an innovative learning model that can be replicated in other schools to support the enhancement of vocational education